Exercise testing for young athletes - Fitzgerald, H.; Fitzgerald, D. A.; Selvadurai, H. (Paediatric Respiratory Reviews, 2025)
With increasing competitiveness across the sporting landscape, there is a need for more research into monitoring and managing the young athlete, as the needs of a young athlete are vastly different to those of an older athlete who is already established in their respective sport. As the age of sports specialisation seems to decrease, exercise testing in the younger cohort of athletes is crucial for safety and long-term success. This article provides a comprehensive summary of available testing and monitoring methods that can be used to assist young athletes as they mature and attempt to excel in their chosen sport.